Corporate Social Reporting: a Comprehensive Picture of Indonesian Mining Companies - Rosinta Ria Panggabean; Nuraini Sari; Lidiyawati Lidiyawati; Evi Steelyana (Bina Nusantara University, 2014)
Recently, stakeholders demand that CSR reporting of a company provides social and environmental information as well as the financial information reported in financial statement. This research questioned whether CSR reporting of Indonesian mining companies may be regarded as a mechanism which social and environmental accountability are discharged. The purpose of this research is to provide a content analysis framework and information on the comprehensiveness of Corporate Social Responsibility (CSR) reporting of Indonesian mining companies. The methodology used is content analysis method by a framework derived from GRI G3.1 Guidelines. Comprehensive reporting contains three types of information for each disclosed CSR item: (i) vision and goals, (ii) management approach, and (iii) performance indicator. The framework was used to assess the comprehensiveness of CSR report by analyzing the 2012 financial reports and annual reports of Indonesian listed mining companies. The content analysis of CSR reporting of the listed mining companies in Indonesia shows a low level of comprehensive reporting. This finding agrees those of prior studies on the completeness of CSR reporting and adds to the debate regarding whether CSR reporting of Indonesian mining companies can be considered a mechanism for discharging social and environmental accountability.